Morphometric Study of the Small Intestine in Two Types of Bird’s Guinea Fowl (Numidia Meleagris) and Falcon (F. Tinnunculus) - Al-Basheer, Ali. H.; Al-Samawy, Eyhab R. M. (American Journal of Biomedicine and Pharmacy, 2024)
The small intestine in studied birds consists from three part (duodenum, jejunum, and ileum). The small intestine extended from the pyloric portion of the gizzard to the junction with large intestine .It was appeared as a coiled mass of long tube forming series loops inside the coelomic cavity. Only the duodenum was obvious towards the right side of the coelomic cavity , while the other parts of small intestine jejunum and ileum were covered partially by duodenal loop. The duodenum was distinct form of a characteristic U-shape tube, consisted of proximal "descending" and distal "ascending" arms forming loops of the duodenum. The small intestine become coiled and structured a number of short garland-like coiled at the dorsal edge of a thin mesentery towards the dorsal part of coelomic cavity to form the jejunum which was the longest part of small intestine in current study that have pinkish gray color guinea fowl and in falcon show dark pink part. Ileum of studied birds were the third part of the small intestine. It appeared as a reddish gray to yellowish straight short structure and it was shorter than the previous parts of small intestine.